The structural basis of N-acyl-α-amino-β-lactone formation catalyzed by a nonribosomal peptide synthetase - Dale F. Kreitler (Nature Portfolio, 2019)
The antimicrobial β-lactone obafluorin is produced by a Nonribosomal Peptide Synthetase (NRPS). Here the authors present the crystal structure of the obafluorin NRPS and develop a reconstitution assay that allows them to analyse product formation from obafluorin NRPS mutants and alternate substrates.